The Effect of Reflective Clinical Learning with Mind Map on Critical Thinking Students at the Nursing Profession Program in Yogyakarta - Ernawati, Yuli; Dewi, Ika Mustika (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Critical thinking skills must be improved and need to be started from the education stage. Mind map has been used as a learning method which is expected to improve the ability of prospective professional nurses in terms of critical thinking. The purpose of this study was to determine the effect of reflective clinical learning with mind map on the critical thinking skills of nursing students in Yogyakarta.Method: This was a quantitative study with a quasi-experimental design, pretest and posttest design with non-equivalent control groups. The research subject was a student in nursing profession program which found 40 people who were selected by purposive sampling. The research data collection was carried out in September-October 2022. The instrument used a critical thinking disposition self-rating form which was measured by a ratio scale.Results: A statistical test results paired t-test showed critical thinking skills in the intervention group, p-value = 0.144 (> 0.05) which means there is no significant difference in the average before and before treatment. With the same statistics, showing the critical thinking ability of the control group, p-value = 0.531 (> 0.05) which means there is also no significant difference in the average before and before the test in the group.Conclusions: Although there was no significant difference in the critical thinking ability of respondents between pre and post-test both the control group and the experimental group, there was an increase in the average score in experimental group after intervention, but in the control group it decreased at the post-test.